Peningkatan Omset Usaha Pelaku UMKM Melalui Digital Marketing Di Wisata Ciung Wanara Kabupaten Ciamis, Jawa Barat: Increasing Business Turnover of MSMEs Through Digital Marketing In Ciung Wanara Tour, Ciamis Regency, West Java - Mohammad Ruvi; Aep Saefullah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service aims to assist 25 Micro, Small, and Medium Enterprises (MSMEs) in the Ciung Wanara tourist location, Ciamis district, boost their sales turnover in 2022. The method is carried out by providing socialization, offline discussions, and training, as well as digital materials. Make-up. Micro, Small, and Medium Enterprises (MSMEs) are an important part of the Indonesian economy. This type of business is very stable, not affected by inflation, flexible, and not overly reliant on the macro-financial system. The role of digital marketing facilitates MSME actors' ability to provide information and interact directly with consumers, expand market share, raise awareness, and increase sales turnover. MSME actors in Ciung Wanara gain insight as well as depth of understanding into digital marketing as a result of this community service. They already have business Google accounts, Instagram accounts, and other accounts on social media to reach out to a larger viewer.